(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
The present study investigates optimum conditions for Microwave assisted extraction (MAE) of 6-gingerol. Ginger was dried using a cross flow dryer at 55 ± 2 0C for eight hours. Ginger powder was extracted at three different watts (400 W, 500 W, and 600 W), temperatures (50 0C, 60 0C, 70 0C) and time (10, 20, 30 min) for optimum yield. 6-gingerol content was found to be 21.15 ± 0.13 and 18.81 ± 0.15 mg/g in fresh ginger and dried ginger, respectively. Optimized condition obtained by RSM for 6-gingerol was 400 W, 70 0C at 10 min extraction time. The results of MAE are expressed by 2-D contour plot and response surface curve by keeping one variable constant which showed highest yield at 600 W, 70 0C for 30 min extraction time. Microwave assisted extracts exhibited higher antioxidant activity in comparison with conventional extracts.